Cholangiocyte autophagy contributes to hepatic cystogenesis in polycystic liver disease and represents a potential therapeutic target. Issue 3 (1st February 2018) - Masyuk, Anatoliy I.; Masyuk, Tatyana V.; Lorenzo Pisarello, Maria J.; Ding, Jingyi (Francess); Loarca, Lorena; Huang, Bing Q.; LaRusso, Nicholas F.
Abstract : Polycystic liver disease (PLD) is a group of genetic disorders with limited treatment options and significant morbidity. Hepatic cysts arise from cholangiocytes exhibiting a hyperproliferative phenotype. Considering that hyperproliferation of many cell types is associated with alterations in autophagy, we hypothesized that autophagy is altered in PLD cholangiocytes, contributes to hepatic cystogenesis, and might represent a potential therapeutic target. We employed functional pathway cluster analysis and next‐generation sequencing, transmission electron microscopy, immunofluorescence confocal microscopy, and western blotting to assess autophagy in human and rodent PLD cholangiocytes. A three‐dimensional culture model was used to study the effects of molecular and pharmacologic inhibition of autophagy on hepatic cystogenesis in vitro, and the polycystic kidney disease–specific rat, an animal model of PLD, to study the effects of hydroxychloroquine, a drug that interferes with the autophagy pathway, on disease progression in vivo . Assessment of the transcriptome of PLD cholangiocytes followed by functional pathway cluster analysis revealed that the autophagy–lysosomal pathway is one of the most altered pathways in PLD. Direct evaluation of autophagy in PLD cholangiocytes both in vitro and in vivo showed increased number and size of autophagosomes, lysosomes, and autolysosomes; overexpression of autophagy‐related proteins (Atg5, Beclin1, Atg7, and LC3); and enhanced autophagic flux associated with activation of the cAMP–protein kinase A–cAMP response element–binding protein signaling pathway. Molecular and pharmacologic intervention in autophagy with ATG7 small interfering RNA, bafilomycin A1, and hydroxychloroquine reduced proliferation of PLD cholangiocytes in vitro and growth of hepatic cysts in three‐dimensional cultures. Hydroxychloroquine also efficiently inhibited hepatic cystogenesis in the polycystic kidney disease–specific rat. Conclusion: Autophagy is increased in PLD cholangiocytes, contributes to hepatic cystogenesis, and represents a potential therapeutic target for disease treatment. (Hepatology 2018;67:1088–1108)